Inhibiting β-Catenin by β-Carboline-Type MDM2 Inhibitor for Pancreatic Cancer Therapy - Qin, Jiang-Jiang; Wang, Wei; Li, Xin; Deokar, Hemantkumar; Buolamwini, John K.; Zhang, Ruiwen (Frontiers in Pharmacology, 2018)
The β-catenin and MDM2 oncoproteins are overexpressed and constitutively activated in human pancreatic cancer and contribute to its initiation, progression, and metastasis. The Wnt/β-catenin signaling pathway strongly interacts with the MDM2-p53 signaling pathway, accelerating the tumorigenesis and its development. Therefore, therapies inhibiting both β-catenin and MDM2 are suggested to be ideal treatments for patients with advanced pancreatic cancer. We have recently identified a novel class of β-carboline compounds as the specific and potent MDM2 inhibitors, including a lead compound SP141. In the present study, we utilized SP141 as an exemplary β-carboline compound to characterize β-catenin as a molecular target of the β-carboline compounds and to demonstrate an important role of β-catenin in the anticancer activity of β-carboline. We found that the silencing of either β-catenin or MDM2 largely reduced the anticancer activity of SP141 while the double silencing of both genes almost completely blocked SP141’s activity. SP141 directly bound to β-catenin and inhibited its expression and activity in pancreatic cancer cells in vitro and in vivo. The inhibitory effects of SP141 on β-catenin were mediated by the ubiquitin-proteasome system in an MDM2-independent manner. In conclusion, these results suggest that SP141 exerts its anticancer activity by dually inhibiting β-catenin and MDM2. We envision that β-carboline derivatives can be developed as promising dual inhibitors of β-catenin and MDM2 for the treatment of advanced pancreatic cancer.